Plasma Membrane Localization Is Required for RasA-Mediated Polarized Morphogenesis and Virulence of Aspergillus fumigatus - Fortwendel, Jarrod R. (American Society for Microbiology, 2012)
Ras is a highly conserved GTPase protein that is essential for proper polarized morphogenesis of filamentous fungi. Localization of Ras proteins to the plasma membrane and endomembranes through posttranslational addition of farnesyl and palmitoyl residues is an important mechanism through which cells provide specificity to Ras signal output. Although the Aspergillus fumigatus RasA protein is known to be a major regulator of growth and development, the membrane distribution of RasA during polarized morphogenesis and the role of properly localized Ras signaling in virulence of a pathogenic mold remain unknown. Here we demonstrate that Aspergillus fumigatus RasA localizes primarily to the plasma membrane of actively growing hyphae. We show that treatment with the palmitoylation inhibitor 2-bromopalmitate disrupts normal RasA plasma membrane association and decreases hyphal growth. Targeted mutations of the highly conserved RasA palmitoylation motif also mislocalized RasA from the plasma membrane and led to severe hyphal abnormalities, cell wall structural changes, and reduced virulence in murine invasive aspergillosis. Finally, we provide evidence that proper RasA localization is independent of the Ras palmitoyltransferase homolog, encoded by erfB, but requires the palmitoyltransferase complex subunit, encoded by erfD. Our results demonstrate that plasma membrane-associated RasA is critical for polarized morphogenesis, cell wall stability, and virulence in A. fumigatus.